Chronic exposure to inhaled vaporized cannabis high in Δ9-THC suppresses Adderall-induced brain activity - Ognibene, Jack M.; Desai, Rajeev I.; Kulkarni, Praveen P.; Ferris, Craig F. (Frontiers in Pharmacology, 2024)
Background: The misuse of prescription psychostimulants for cognitive enhancement together with recreational cannabis is increasing. Does the chronic use of cannabis high in Δ9-THC alter the sensitivity to amphetamines. We hypothesized chronic exposure to Δ9-THC through vaporized cannabis would diminish the CNS activity of Adderall. Methods: We exposed male and female mice to inhaled vaporized cannabis (10.3% Δ9-THC) or placebo for 30 min each day for ten consecutive days. After twenty-four hours, mice were imaged fully awake for changes in BOLD signal following an IP injection of Adderall (60 µg) during the scanning session. After a two-week washout, without any cannabis or placebo exposure, mice were again imaged and challenged with Adderall during the scanning session. The data were registered to a mouse 3D MRI atlas with 134 brain regions providing site-specific increases and decreases in global brain activity. Results Mice exposed to cannabis when compared to placebo showed a decrease in brain activation to Adderall. The blunted Adderall response was characterized by a decrease in positive BOLD signal and increase in negative BOLD. The prefrontal cortex, accumbens, ventral pallidum, caudate/putamen, and thalamus were most affected. After a two-week wash out there were no significant differences between the cannabis and placebo groups when challenged with Adderall. Summary This exploratory study shows that short, daily exposures to inhaled cannabis, something equivalent to recreational use, affects the sensitivity to the psychostimulant Adderall. The reduced Adderall effect on brain activity, particularly circuitry associated with dopaminergic signaling raises concerns about escalation in psychostimulant use.